Utilization Of Moringa Seed Oil Fatty Acids for Azelaic Acid Base Stock Production - Erin Ryantin Gunawan; Dedy Suhendra; Murniati Murniati; Dhony Hermanto; Liliek Karnila; Sri Seno Handayani (Postgraduate, University of Mataram, 2022)
Moringa (Moringa oleifera L.) is a plant belonging to the moringaceae family. Moringa seeds contain oil which can be used as a raw material for making azelaic acid. Azelaic acid is used as an anti-acne in the pharmaceutical and cosmetic industries. Azelaic acid can be obtained from the oxidation process of fatty acids in moringa seed oil using potassium permanganate as an oxidizing agent. The resulting azelaic acid is in the form of white crystals with a conversion percentage of 72.17%. The results of the FT-IR characterization showed the formation of azelaic acid characterized by widening of the hydroxyl group at 3448.46 cm-1 followed by a shift of the ester group at absorption of 1633.46 cm-1. The ester bond is strengthened at a wavelength of 1115.95 cm-1.